Immobilization and Application of the Recombinant Xylanase GH10 of Malbranchea pulchella in the Production of Xylooligosaccharides from Hydrothermal Liquor of the Eucalyptus (Eucalyptus grandis) Wood Chips - Alnoch, Robson C.; Alves, Gabriela S.; Salgado, Jose C. S.; de Andrades, Diandra; Freitas, Emanuelle N. de; Nogueira, Karoline M. V.; Vici, Ana C.; Oliveira, Douglas P. [UNESP]; Carvalho-Jr, Valdemiro P. [UNESP]; Silva, Roberto N.; Buckeridge, Marcos S.; Michelin, Michele; et al. (MDPI, 2022)
Xylooligosaccharides (XOS) are widely used in the food industry as prebiotic components. XOS with high purity are required for practical prebiotic function and other biological benefits, such as antioxidant and inflammatory properties. In this work, we immobilized the recombinant endo-1,4-β-xylanase of Malbranchea pulchella (MpXyn10) in various chemical supports and evaluated its potential to produce xylooligosaccharides (XOS) from hydrothermal liquor of eucalyptus wood chips. Values >90% of immobilization yields were achieved from amino-activated supports for 120 min. The highest recovery values were found on Purolite (142%) and MANAE-MpXyn10 (137%) derivatives, which maintained more than 90% residual activity for 24 h at 70 °C, while the free-MpXyn10 maintained only 11%. In addition, active MpXyn10 derivatives were stable in the range of pH 4.0–6.0 and the presence of the furfural and HMF compounds. MpXyn10 derivatives were tested to produce XOS from xylan of various sources. Maximum values were observed for birchwood xylan at 8.6 mg mL−1 and wheat arabinoxylan at 8.9 mg mL−1, using Purolite-MpXyn10. Its derivative was also successfully applied in the hydrolysis of soluble xylan present in hydrothermal liquor, with 0.9 mg mL−1 of XOS after 3 h at 50 °C. This derivative maintained more than 80% XOS yield after six cycles of the assay. The results obtained provide a basis for the application of immobilized MpXyn10 to produce XOS with high purity and other high-value-added products in the lignocellulosic biorefinery field.
Keywords: Eucalyptus grandis; hydrothermal liquor; immobilization; Malbranchea pulchella; xylanases; xylooligosaccharides